2021
DOI: 10.1128/jvi.02154-20
|View full text |Cite
|
Sign up to set email alerts
|

A Replication-Defective Influenza Virus Harboring H5 and H7 Hemagglutinins Provides Protection against H5N1 and H7N9 Infection in Mice

Abstract: The recent highly pathogenic avian influenza (HPAI) H5N1 and H7N9 viruses have caused hundreds of human infections with high mortality rates. Although H5N1 and H7N9 viruses have been mainly limited to avian species, there is high potential for these viruses to acquire human-to-human transmission and initiate a pandemic. A highly safe and effective vaccine is needed to protect against a potential H5N1 or H7N9 influenza pandemic. Here, we report the generation and evaluation of two reassortant influenza viruses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The research found that the 5' and 3' packaging signals of each vRNA segment of the influenza virus are crucial to assemble a progeny virion with newly synthesized vRNA segments. Previously, one group reported an approach for the generation of a reassortant chimeric replication-defective influenza virus which grew well in vitro through the addition of bacterial sialidase and provided protection against H5N1 and H7N9 infection in mice (Tian et al, 2021 ). Based on this information, it is workable to generate a genome-modified LAIV.…”
Section: Discussionmentioning
confidence: 99%
“…The research found that the 5' and 3' packaging signals of each vRNA segment of the influenza virus are crucial to assemble a progeny virion with newly synthesized vRNA segments. Previously, one group reported an approach for the generation of a reassortant chimeric replication-defective influenza virus which grew well in vitro through the addition of bacterial sialidase and provided protection against H5N1 and H7N9 infection in mice (Tian et al, 2021 ). Based on this information, it is workable to generate a genome-modified LAIV.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the low-pathogenicity avian influenza virus has only one alkaline arginine at the HA cleavage site and can be cleaved by trypsin-like proteases present in the respiratory and digestive tracts; therefore, the virus is generally restricted to replication in the respiratory and digestive tracts [65,66]. The highly pathogenic H5 and H7 subtype avian influenza viruses have multiple consecutive alkaline amino acids at the HA cleavage site that can be cleaved by proteases widely present in cells, which potentially leads to systemic infection [67]. A reverse genetic system was used to remove multiple basic amino acids from the HA cleavage site of highly pathogenic avian influenza virus, and the results showed that the virus's pathogenicity in poultry and mice was reduced [68].…”
Section: Reverse Genetic Technology Use In Influenza Virus Pathogenicity Researchmentioning
confidence: 99%
“…Newer H5N1 and H7N9 vaccine candidates are being investigated to protect against a potential pandemic. For example, two reassortant influenza vaccines expressing H5 or H7 HAs (PR8-H5-H7NA and PR8-H7-H5NA) have been shown to replicate to high titers when exposed to exogenous neuraminidase (NA) in vitro, and these vaccine candidates were shown to be replication-defective and nonvirulent when administered intranasally in mice [ 19 ]. Vaccination with PR8-H5-H7NA elicited robust immune responses to H5 and H7 viruses and conferred complete protection against H5N1 and H7N9 challenges in mice.…”
Section: Introductionmentioning
confidence: 99%